Applying biochar under topsoil facilitates soil carbon sequestration: A case study in a dryland agricultural system on the Loess Plateau - Li, Shuailin; Ma, Qiang; Zhou, Changrui; Yu, Wantai; Shangguan, Zhouping (Geoderma, 2021)
•The effect of biochar application depth on soil CO2 and CH4 fluxes was examined.•Soil respiration and CH4 uptake highly depend on the soil environment at 0–10 cm.•Biochar incorporation into the 10–20 cm depth promoted soil C sequestration. The remarkable soil carbon sequestration and greenhouse gas mitigation effects of biochar have spurred great interest in exploring ways to maximize its benefits. However, it remains unclear how biochar application depth impacts soil carbon dioxide (CO2) emissions and methane (CH4) uptake in upland soil. Therefore, we carried out a 16-month field experiment in a dryland agricultural system to answer the above questions. Woody biochar (20 t ha−1) was mixed into three soil layers: 0–10 cm (BC0-10cm), 10–20 cm (BC10-20cm), and 0–20 cm (BC0-20cm). Soil without biochar addition was used as the control (CK). We monitored soil CO2 and CH4 fluxes continuously and determined the metabolic quotient (qCO2) and the sensitivity of soil respiration to temperature (Q10). The results indicated that CO2 emissions, CH4 uptake, qCO2 and Q10 were significantly affected by biochar application depth. Overall, compared with CK, BC0-10cm increased total CO2 emissions by 10.13%, while BC10-20cm and BC0-20cm showed no significant effect. BC0-10cm and BC0-20cm exhibited greater soil CH4 uptake enhancement than BC10-20cm, but the enhanced CH4 uptake resulted in limited net greenhouse gas mitigation. BC10-20cm and BC0-20cm had a lower qCO2 than the other treatments, which likely increased the carbon use efficiency and decreased the stress on soil microbes, but BC0-10cm showed the opposite effect. In addition, BC0-10cm significantly reduced Q10 mainly due to the enhanced lability of the native carbon and microbial activities. Changes in environmental factors in the 0–10 cm soil largely explained the variations in CO2 emissions, CH4 uptake and Q10 (>88%). Nevertheless, the enhanced microbial biomass in the 10–20 cm soil helped lower qCO2 in the whole 0–20 cm layer. In summary, adding biochar to surface soil (0–10 cm) likely accelerates carbon loss, due to the strong shift in the environment of the surface soil caused by complex interactions among hydrothermal conditions, nutrient levels (i.e., N, NH4+, NO3− and available P) and labile carbon. However, adding biochar to subsurface soil (10–20 cm) can effectively avoid severe disturbance of the surface soil environment and thus benefit soil carbon sequestration in the long term.